Evaluation of nitrogen oxide emissions and smoke opacity in a HSDI diesel engine fuelled with palm oil biodiesel - Agudelo, John; Benjumea, Pedro; Villegas, Adriana Patricia (Revista Facultad de Ingeniería Universidad de Antioquia, 2013)
In this paper, an experimental study evaluating engine performance, nitrogen oxide emissions (NOx) and smoke opacity of a HSDI (high speed direct injection) diesel engine fuelled with neat palm oil biodiesel (POB) is presented. Tests were performed in a bench-mounted automotive diesel engine operating under steady state conditions. Conventional diesel fuel was taken as base line or reference fuel. Results show that at full-load operation POB led to a power output decrease between 10% and 17% and an effective specific fuel consumption increase between 14% and 22%. At full-load and low engine speeds an increase of 20% in NOx emissions was measured. However, at the same torque rating and high engine speeds a 6% decrease in such emissions was obtained. At partial-load, NOx emissions always increased using POB, this effect being more pronounced at low speeds. On the other hand, smoke opacity significantly decreased (between 40% and 80%) regardless of engine load. According to the experimental results POB fuelling reduced engine power output, increased fuel consumption, increased slightly efficiency, always decreased smoke opacity, and reduced or increased NOx emissions depending on the engine operation mode.